Oil monarchies domestic and security challenges in the Arab Gulf States - Gause, F. Gregory (A Council on Foreign Relations book, 1994)
This timely book demystifies the politics of Saudi Arabia, Kuwait, Bahrain, Qatar, United Arab Emirates, and Oman, and focuses on the new pressures that have emerged since the Gulf War. Gause illuminates the foreign policy tightrope these states walk in the Middle East: self-defense is problematic, regional pressures translate directly into the domestic arena, and relations with the United States can cause as well as solve problems. Gause examines the interplay of Islamic fundamentalism, tribalism, and, most importantly, oil wealth that has determined the power structure of the Gulf monarchies. He shows what influences really drive politics in the Middle East as well as how U.S. foreign policy must respond to them in order to forge more meaningful ties with each country and preserve the stability of a fragile region that is vital to U.S. interests.